Enzymatic characterization of blood lymphocytes in various clinical and pathogenetic variants of respiratory allergy - A. M. Lazareva; O. A. Kolenchukova; S. V. Smirnova (Медицинская иммунология, 2021)
Allergy is a sufficient social and economic issue of modern times. Altered immunity in allergic disorders is based, mainly, on the lymphocyte disturbances.Immune characteristics depend both on populations and subpopulational profile of immune cells, and on intrinsic intensity and specific features of theirintracellular metabolism. Interest to studies of intracellular metabolism of lymphocytes id determined by high-scale energetic and plastic processes aimed for support of immune homeostasis. The aim of this study was to evaluate the state of intracellular metabolism in peripheral blood lymphocytes from the patients with respiratory allergies of different genesis and respiratory affection.The study included patients with various clinical variants of respiratory allergy (n = 152) at the age of 21 to 63 years old, and virtually healthy blood donors (n = 209), comparable for age and sex. Within these cohorts, we have separately analyzed, e.g., respiratory atopy (atopic rhinosinusitis and atopic bronchial asthma), as well as respiratory pseudoatopy (polypous rhinosinusitis and asthmatic triad). Allergic disorders of upper respiratory ways were diagnosed in a complex clinical examination by allergologist/immunologist and otorhinolaryngologists. Bronchial asthma verification was based on current GINA criteria (2014). We used m standard common clinical methods and specific allergological diagnostics, e.g., allergological anamnesis, skin prick tests, with different non-infectious allergens, measurement of total and specific IgE’s with ELISA method. The parameters of intracellular metabolism of peripheral blood lymphocytes were determined with bioluminescent technique with bacterial luciferase. Actifity of NAD(P) and NAD(P)H enzymes was measured.Dehydrogenase activities in lymphocytes were expressed as enzyme un its (EU, 1 unit = 1 mcmol/min) per 104 cells.Certain changes of intracellular activities in peripheral lymphocytes are revealed, dependent on genesis and origin of allergic inflammation, and affection level of respiratory ways. In respiratory atopy (atopic rhinosinusitis and atopic bronchial asthma), irrelevant on the level of respiratory affection, the activities of intracellular enzymes suggest increased plastic processes that are maximally pronounced in atopic bronchial asthma. In respiratory pseudoatopy (polypous rhinosinusitis and asthmatic triad) the metabolic changes of lymphocytes presume activation of both plastic and energetic processes, with decreased intensity in asthmatic triad condition. Independent on genesis of respiratory allergic inflammation, we have determined low activity of NAD(P)-dependent glutamate dehydrogenase, and NAD(H)-dependent lactate dehydrogenase in allergic inflammation of upper respiratory ways (atopic rhinosinusitis and polypous). Its activity is statistically higher in bronchial asthma (atopic bronchial asthma and asthmatic triad.